125x3+343y3 can also be written (5x)3+(7y)3. It helps to rewrite the constants like this because there is a general factoring rule: a3+b3 = (a+b)(a2-ab+b2). In this example, the a is 5x and the b is 7y. Plug in and get (5x+7y)(25x2-35xy+49y2).
The answer is 383
125x3 + 1 ???????? 53 * x3 + 1 ================?????
no
(4x + 7y)(16x2 - 28xy + 49y2)
(5x - 2)(25x^2 + 10x + 4)
(5x + y)(25x^2 - 5xy + y^2)
343y3
In order to factor the sum of the cubes, we need to use this form a³ + b³ = (a + b)(a² - ab + b²). Let a³ = 27x³ and b³ = 343y³. Then, a = 3x and b = 7y. Perform substitution of these terms for the form, and we obtain: 27x3 + 343y3 = (3x + 7y)(9x2 - 21xy + 49y2)
125x3, because you have to times the x too. So it's like (5x)(5x)(5x) and what do you get? 125x3!!
5m
The other factor is 1.
(a + 2b)(a + 2b)